Exploring the Endocannabinoid System: From Circadian Rhythms to Sleep Regulation and Potential Therapeutic Insights - D'Angelo Martina; Steardo Luca (Journal of Sleep And Sleep Disorder Research, 2024)
A state‑of‑the‑science review links the endocannabinoid system to circadian regulation and sleep physiology, examining therapeutic prospects and research gaps.
Keywords: sleep disturbance